Pengaruh Akuntabilitas, Transparansi dan Partisipasi Terhadap Pengelolaan Dana Desa di Desa Sei Mencirim Kecamatan Sunggal Kabupaten Deli Serdang - Ananda, Fadia; Nasution, Dito Aditia Darma; Supraja, Galih (Indo-MathEdu Intellectuals Journal, 2025)
The research aims to determine the influence of accountability, transparency, and community participation on the management of village funds in Sei Mencirim, Sunggal District, Deli Serdang Regency. The type of research used is quantitative. Primary data collection was conducted using questionnaires. The sample in this study consisted of 30 respondents. This study uses multiple linear regression analysis. The test results for the accountability variable indicate that accountability has a positive and significant partial effect on the management of village funds. The test results for the transparency variable indicate that transparency has a positive and significant partial effect on the management of village funds. The test results for the community participation variable indicate that community participation does not have a significant partial effect on the management of village funds. The simultaneous testing results show a calculated F value of 22.571, which is greater than 2.98, and a significance value of 0.000, which is less than 0.05, thus it can be concluded that accountability, transparency, and community participation have a significant simultaneous effect on the management of village funds in Sei Mencirim, Sunggal District, Deli Serdang Regency.